Simulation Study for Syn-Gas Productivity of Open Top Downdraft Gasifier Using Wood Sawdust Feedstock by ASPEN Plus - Halid Nuryadi; Kamaruddin Abdullah; Syukri M Nur (Journal of Applied Sciences and Advanced Technology, 2022)
Wood sawdust feedstock is one of commodity of furniture industrial waste in Indonesia. It could be used for biomass feedstock for syn-gas producing with gasification process. Wood sawdust could be alternative ways for replacing other biomass feedstock that hard to find for biomass gasification processing, it has good high heating value (HHV) of abouts 18.75 MJ/kg. Besides that open top downdraft gasifier is one of a kind biomass gasifier/reactor for syn-gas producing. It had better with the other gasifier for syn-gas producing; such as cross draft gasifier and updraft gasifier because for micro-grid electricity it has lower cost for designing and maintaining. Syn-gas is a synthetic gas that contains several elements of hydrocarbons, such as CO (carbon monoxide), CH4 (methane) and H2 (hydrogen). It could be useful for combining with internal combustion engine for producing micro-grid electricity. Syn-gas could be alternative fuel to replace gasolines or diesels fuel for internal combustion engine that converted to electrical generator as prime mover power. At this simulation study we get the result of mole fractions for syn-gas productivity from wood sawdust feedstock by using ASPEN Plus software is CO (1.622%), CH4 (6.722%), H2 (12.448%). At the end of the calculations we get HHV of syn-gas is 4.47 MJ/Nm3, gasification efficiency (Xcge) is 20% and amount of carbon in wood sawdust that convert to gaseous (Xc) is 0.43%. Simulation study by using ASPEN Plus software could be more useful for resulting syn-gas productivity without any problems. For academic communities, simulation study by using software could be solutions when we have no more cost for practicing in the workshop.